THE ROLE OF HYPERBARIC THERAPY IN THE GROWTH OF CANDIDA ALBICANS - Widiyanti, Prihartini (Indonesian Journal of Tropical and Infectious Disease, 2013)
Background: Candida albicans is opportunistic pathogen fungi which cause many disease in human such as reccurrent apthous stomatitis, skin lesions, vulvavaginitis, candiduria and gastrointestinal candidiasis. Aim: Infection mechanism of C. albicans is very complex including adhesion and invasion, morphology alteration from khamir form cell to filamen form (hifa), biofilm forming and the avoidance of host immunity. Method: The ability of C. albicans to adhere to the host cell which is act as important factor in the early colonization and infection. Result: The phenotype alteration to be filament form let the C. albicans to penetrate to the epithelium and play important role in infection and separation C. Albicans to the host cell. Hyperbaric oxygen is the inhalation of 100 percent oxygen inside hyperbaric chamber that is pressurized to greater than 1 atmosphere (atm). Conclusion: The organism was found to be inhibited within a pressure/time range well tolerated by human subjects, suggesting that hyperbaric oxygen might be used successfully in treating human candidiasis.